2006
DOI: 10.1159/000089730
|View full text |Cite
|
Sign up to set email alerts
|

Can the Effect of Antibiotherapy and Anti-Inflammatory Therapy on Serum PSA Levels Discriminate between Benign and Malign Prostatic Pathologies?

Abstract: Objective: The primary aim was to evaluate the change in the total and free PSA levels after antibiotic and non-steroid anti-inflammatory treatment. The secondary aim was to compare this change among the histological subgroups to assess whether it was discriminating. Methods: 97 consecutive patients with PSA >4 ng/dl and scheduled for prostate biopsy were included in this prospective study. 65 patients (group 1) were then put on medical treatment of ciprofloxacin 500 mg bid and diclofenac sodium 75 mg during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Ciprofloxacin is commonly prescribed with analgesics for the management of infection, pain and inflammation. Co-medication with ciprofloxacin and diclofenac occurs in many clinical situations [12][13][14] . Several reports have shown that co-administration of ciprofloxacin significantly decreased exposure of mycophenolic acid [15,16] , partly by inhibiting β-glucuronidase [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin is commonly prescribed with analgesics for the management of infection, pain and inflammation. Co-medication with ciprofloxacin and diclofenac occurs in many clinical situations [12][13][14] . Several reports have shown that co-administration of ciprofloxacin significantly decreased exposure of mycophenolic acid [15,16] , partly by inhibiting β-glucuronidase [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The difference between pre-and post-treatment PSA levels appears significant only in benign conditions (BPH and prostatitis cases), while in histologically proven cancer cases the difference seems unremarkable [20] . NIH category IV CP appears to contribute to increased PSA levels even if no bacteria are found in expressed prostatic secretion [6] ; nevertheless, Magri et al [21] observed a 34.6% PSA reduction after antibiotics and Terrone et al [22] showed that the indication to biopsy subsided in 20-30%.…”
Section: Prostatitis and Pca Detection At Repeated Biopsymentioning
confidence: 88%
“…An elevated PSA level is reported to be related to prostatitis [4,6,7,12], and prostate inflammation is known to be a main reason for compromise of the specificity of PSA [13]. Many studies have shown that treatment of chronic prostatitis can decrease the PSA level, which suggests that the use of antimicrobial or nonsteroidal anti-inflammatory agents may reduce the number of men who require prostate biopsy [6,7].…”
Section: Discussionmentioning
confidence: 99%